The Chinese Yuan Special Drawing Right Basket and Currency Risk Management - Hassanain, Khalifa (International Journal of Economics and Financial Issues, 2017)
The focus of this short paper is on SDR based currency risk management including the choice of the appropriate currency index, pattern of adjustment of currency weights following financial shocks and the exchange rates to be used in the process of calculations. The new change in the SDR basket, namely the introduction of the Yuan, may introduce new challenges to currency risk management at MDBs and other institutions using SDR to hedge against currency fluctuations. This study analyze the impact of including the Yuan in the SDR currency basket compared to original no Yuan basket and the change the introduction of the Yuan make on the characteristics of the SDR and other proposed indices (adjustment pattern, Stability and return). The study covers the period 2000-2016. The overall result suggest that the Yuan basket will be less volatile but will have limited impact on SDR dominated assets and the stability of their value. Keywords: SDR, Currency Risk, MDBs JEL Classifications: F13, F31, F33, G32